The Divine Height of Words (On a Couple of Words in the English Translations of Crime and Punishment) - Tatiana A. Boborykina (Достоевский и мировая культура: Филологический журнал, 2023)
The essay explores problems of translating Russian classical Literature into English. It happens that even one word is capable of changing if not the plot, then the profound philosophical message of a text. The double meaning, direct and indirect, of certain words, and their connections with other parts of the text that remain unnoticed, eventually lead to oversimplifying and narrowing the dimension and scale of the composition as a whole in the perception of readers incapable of comprehending the original. Comparative analyses of only two words in several translations of Dostoevsky’s Crime and Punishment show the complexity and the responsibility of translations, especially the translation of a literary work, where the words rise into “divine height” of their signified and hidden meanings.